A herbicide resistance risk matrix. (January 2019) - Moss, Stephen; Ulber, Lena; Hoed, Ingrid den
Abstract: Herbicide resistance is of increasing concern, especially as there is a lack of new modes of action. An assessment of resistance risk has been a key part of the pesticide authorisation process in most European countries since the early 2000's. However, little guidance is provided on how to quantify these risks. The risk matrix described here presents a quantitative approach to the evaluation of the resistance risk posed by the use of herbicides. The inherent, 'unmodified' risk is first assessed by ranking herbicides and major target weed species on a scale from low to high resistance risk, based largely on published information. In practice, agronomic management practices ('modifiers') will reduce the risk and these are factored into the matrix. Modifiers can include management strategies relating to herbicide use as well as non-chemical methods of weed control. By assigning defined impact factors to possible agronomic modifiers, the overall resistance risk of a herbicide under defined use conditions can be quantified. The approach, although simple, appears robust and produces realistic assessments of the resistance risks associated with four contrasting test scenarios. The aim is to achieve a better harmonisation of herbicide resistance risk assessment across Europe. Although the matrix has a European legislative focus, the approach and principles are relevant in other parts of the world where the extensive use of herbicides is a relatively recent development, and where there is currently limited knowledge and expertise on herbicide resistance and the evaluation of resistance risks. Highlights: This risk matrix quantifies the resistance risk posed by the use of herbicides. This aims to better harmonise herbicide resistance risk assessment across Europe. The inherent risk is assessed by ranking herbicides and weeds from low to high risk. Management practices reduce this risk and are factored into the matrix. The approach is also relevant to resistance risk evaluation elsewhere in the world.